Determination of Fluoride Levels and pH in Community Drinking Water Supply across Pune City, Maharashtra - Gandhali Malgaonkar Joshi; Alok Ramesh Patel; Shweta S. Jajoo; Rohan V. Shah; Shweta M. Chaudhary; Laxmi S. Lakade (Wolters Kluwer Medknow Publications, 2024)
Context: The knowledge of fluoride levels and pH in potable water is important for health-care personnel and policymakers in general and dentists in particular, but the data regarding fluoride levels and pH of community drinking water in Pune City are deficient. Aims: The aim of this study was to determine the fluoride levels and pH in community drinking water supply across Pune City, Maharashtra. Subjects and Methods: In an in vitro, experimental study, a total of 30 water samples were collected from one water treatment plant, one water storage reservoir, and three adjoining residential areas of the Pune Municipal Corporation (PMC) and Pimpri Chinchwad Municipal Corporation (PCMC) region. They were analyzed for fluoride content using (2-(parasulfophenylazo)-1,8-dihydroxy-3,6-naphthalene disulfonate) based-spectrophotometric method, and for pH using a digital pH meter. Statistical Analysis Used: Fluoride and pH values were subjected to Mann-Whitney U-test and intragroup comparison of fluoride and pH levels at various levels of water distribution was performed using Kruskal-Wallis test. Results: The mean concentration of fluoride and the pH in water samples from different locations across Pune City were 0.262 and 7.02 mg/L, respectively. Although levels across various sources were different, there was no statistical difference between the fluoride content or the pH of the water from sources across PMC and PCMC regions. Conclusions: The fluoride content of the community water supply of Pune City was below the recommended standards yet within the permissible limits in considering the temperature range in Pune City across different seasons. The pH of the drinking water of Pune City was optimal.